2011
DOI: 10.1016/j.otsr.2011.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of calcaneonavicular coalition in children

Abstract: Calcaneonavicular coalition is a common source of pain and more or less severe flat and stiff foot in children. Classically, treatment consists in resecting the coalition using a dorsolateral approach. Good quality resection and interposition can prevent recurrence. The most common complications are infection, hematoma and neuroma. Arthroscopy offers a minimally invasive alternative, but the optimal approach remains undetermined. We describe a surgical technique with an approach based on the anterolateral proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Fluoroscopy is often not useful for talocalcaneal coalition. Arthroscopic resection has also been reported, 24,25 but involves a long learning curve, 26 longer operating time, 27 , risk of posterior tibial pedicle neurovascular lesion 28 and difficulty in positioning. 29 …”
Section: Application For Tarsal Coalition Resectionmentioning
confidence: 99%
“…Fluoroscopy is often not useful for talocalcaneal coalition. Arthroscopic resection has also been reported, 24,25 but involves a long learning curve, 26 longer operating time, 27 , risk of posterior tibial pedicle neurovascular lesion 28 and difficulty in positioning. 29 …”
Section: Application For Tarsal Coalition Resectionmentioning
confidence: 99%
“…4,5 The first report about endoscopic resection of TCCs was published by Bonasia et al 6 in 2011, and they limited the indication to posterior-facet coalition. On the other hand, Jagodzinski et al 7 reported in 2013 that the lateral approach was useful for middle-facet coalition but had a risk of neurovascular damage for a posterior-facet coalition.…”
mentioning
confidence: 99%
“…Andreasen reported that this technique was associated with satisfactory outcomes for twenty-two of thirty patients who were followed for as long as twenty-two years postoperatively 52 , Chambers et al noted a 100% rate of satisfactory results in a study of twenty-nine patients who were followed for three to fourteen years 55 , Cowell reported good or excellent outcomes for twenty-three (88%) of twenty-six patients 56 , and Gonzalez and Kumar reported good to excellent outcomes for fifty-eight (77%) of seventyfive patients who were followed for an average of three years following resection and interposition 54 . A minimally invasive method of performing a coalition resection with use of arthroscopy 57,58 recently has received attention, with good short-term results being observed in studies involving very small sample sizes 59 . The main concern regarding arthroscopic resection involves adequate identification of the deeper aspect of the osseous coalition bridge, which, if not adequately resected, can facilitate recurrence of coalition.…”
Section: Calcaneonavicular Coalitionsmentioning
confidence: 99%